Nutritional status and its associated factors among children - Masdalena, Masdalena; Nadapdap, Marshall Jeremia (Jurnal Prima Medika Sains, 2023)
This study aimed to analyze the nutritional status of children in these districts, taking into account factors such as age, gender, maternal education, family income, and children's eating patterns. The study used a cross-sectional design, with 279 children aged 1-10 years as subjects. Data were collected by distributing structured questionnaires to the participants’ parents. The data were analyzed using the chi-square test to determine the significance of the relationship between the predictors and nutritional status of the children (α = 0.05). The results showed that maternal education (0.012), parental income (0.001), and eating patterns (0.001) were significantly associated with the nutritional status of children who were stunted and normal. However, for overweight and obese children, maternal education (0.835), parental income (0.951), and eating patterns (0.309) were not predictors of nutritional status. Age and sex did not significantly influence the nutritional status of children in all categories. Family based interventions through health education are needed to improve nutritional literacy so that parents can plan and prepare nutritious meals for their children. The government must provide policies to support families, especially those with low incomes, to ensure the availability of adequate food and access to nutritious food.